Dental Students' Factual and Procedural Knowledge Retention in Operative Dentistry in a Clinical Dental Curriculum. Issue 9 (1st September 2018) - Hausdörfer, Tim; Kanzow, Philipp; Tschammler, Claudia; Herrmann, Manfred; Wiegand, Annette
Abstract : The aim of this study was to evaluate dental students' retention of factual and procedural knowledge gained in a preclinical course in operative dentistry during a clinical dental curriculum. In 2017, all 157 seventh‐ to tenth‐semester dental students at a dental school in Germany were asked to repeat the same written examination performed at the end of the preclinical course in the sixth semester. The examinations consisted of 30 multiple‐choice questions covering factual and procedural knowledge. The percentage of correctly answered questions per exam and differences in correct answers between the original examination and the re‐examination (per question) were analyzed. Students were also asked to self‐rate their percentage of correctly answered questions and their knowledge in various disciplines of operative dentistry at the times of the original examination and the re‐examination. After exclusions, data were analyzed for 129 students, for a participation rate of 82%. For the seventh‐ and tenth‐semester students, the results on the original examination and the re‐examination were not significantly different, while the eighth‐ and ninth‐semester students performed significantly better on the original examination than the re‐examination. In all semesters, procedural knowledge remained stable between the original examination and the re‐examination, while factual knowledge decreased slightly. Their performance on the original examination was underestimated by the eighth‐ and ninth‐semester students. All the students underestimated their performance on the re‐examination. Students mostly rated their knowledge level significantly higher on the original examination than on the re‐examination. Overall, this study found that factual and procedural knowledge gained in a preclinical course in operative dentistry was not increased during the clinical dental curriculum.